Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 4635 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Rostellularia adscendens (R.Br.) R.Barker" ] } The dataset includes 4635 records from 13 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001254-150407101314760/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences